Herbal Approaches to Breast Cancer: Insights from Indian Medicinal Flora – A Review (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Breast cancer is the most common malignancy in women and the second leading cause of cancer deaths. Early detection through screening, such as mammography, ultrasound, and MRI, improves survival rates and treatment options. Awareness and education about risk factors and self-examinations are vital for early diagnosis and treatment. In breast cancer treatment, use of synthetic compounds has several drawbacks, including cancer spread, drug resistance, and side effects. Natural compounds are more effective at targeting and destroying cancer cells, with fewer side effects and a lower likelihood of causing drug resistance. These compounds are crucial for cancer treatment as they promote apoptosis and prevent metastasis, effectively destroying cancer cells and keeping them contained. This review examines medicinal plants with proven anti-cancer properties against breast cancer cells, highlighting several notable plants with potent effects. Researching biological anti-breast cancer agents extensively has the potential to significantly improve treatment outcomes and increase patient survival rates.
Keywords: Breast cancer; Medicinal plants; Apoptosis; Phytochemicals